BRAC Education Programme (BEP) IV: proposal, 2002 - BRAC (© BRAC, 2016)
1. Executive summary 2. Poverty and education in Bangladesh 3. BRAC as an organisation 4. Development of BEP 5. The role of NGOs in the national education system, Sustainability, Cross-cutting issues & themes, Target beneficiaries. 6. Budget.